KELOMPOK DARMA WANITA TENTANG KECEMASAN WANITA YANG MENGHADAPI MENOPAUSE - Tri Suyati; Mudzanatun IKIP PGRI Semarang; Fine Reffiane; Iin Purnamasari (Universitas PGRI Semarang, 2011)
Abstract Menopause is known as the end of having menstruation. Usually, women feel afraid of being menopause. Generally, the indication of being Menopause starts at the end of 40 ?óÔé¼ÔÇ£ 45 years old. Most of women complain and worried about it. Especially for those 50 women who could be classified like; 3 teachers, 1 nurse, 1 bank female officer, and 44 are housewives. And the aged level classification is like; age 40 ?óÔé¼ÔÇ£ 50 years old are 25 women, ages 30 ?óÔé¼ÔÇ£ 39 are 15 women, ages 20 ?óÔé¼ÔÇ£ 29 is 1 woman. This team of community service gives them the training how to overcome if they get the menopause period, and how to protect the frustration of being menopause. This training was done through some discipline of aspects like; through biology, sociology and physiology. The team wants to solve their problems seen from the proper aspect. So that, they will understand that menopause will always happen to them, but they also have prepared how to overcome and protect the frustration of being menopause seen from the aspect of biology, sociology and physiology. ?é?á Key words: menopause, menstruation